2019
DOI: 10.1016/j.annemergmed.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Misuse of Prescribed Opioids: A Systematic Review and Meta-Analysis

Abstract: Increasing opioid prescribing has been linked to an epidemic of opioid misuse. Our objective is to synthesize the available evidence about patient-, prescriber-, medication-, and system-level risk factors for developing misuse among patients prescribed opioids for noncancer pain.Methods: We performed a systematic search of the scientific and gray literature for studies reporting on risk factors for prescription opioid misuse. Two reviewers independently reviewed titles, abstracts, and full texts; extracted dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 89 publications
9
91
2
1
Order By: Relevance
“…Characteristics associated with engagement in indicators of potential extra‐medical opioid use included being younger, male and having a lifetime history of pharmaceutical opioid or illicit SUDs. This is consistent with two recent systematic reviews on the risk factors for prescription opioid misuse and addiction among people with CNCP. Additionally, the identification of these risk factors for indicators of potential extra‐medical opioid use supports clinical guidelines , which suggest careful monitoring of people with substance use histories in management of CNCP with opioids.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Characteristics associated with engagement in indicators of potential extra‐medical opioid use included being younger, male and having a lifetime history of pharmaceutical opioid or illicit SUDs. This is consistent with two recent systematic reviews on the risk factors for prescription opioid misuse and addiction among people with CNCP. Additionally, the identification of these risk factors for indicators of potential extra‐medical opioid use supports clinical guidelines , which suggest careful monitoring of people with substance use histories in management of CNCP with opioids.…”
Section: Discussionsupporting
confidence: 92%
“…Monitoring of indicators of potential extra‐medical opioid use is important because they may indicate problems with pain management and are potentially associated with adverse clinical outcomes . Two recent systematic reviews examined the characteristics associated with ‘opioid misuse’ and opioid addiction . Both reviews identified similar significant associations, such as a history of substance use .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of opioids increased as age increased, which is easily understood because the disease burden increases as age increases. It should be taken into account that the misuse of psychoactive substances (mostly illegally obtained) is prevalent among young male users [24]. This fact may be the explanation for the differences between Europe and America concerning death due to opioid misuse, which is particularly common among middle-aged individuals in America [6].…”
Section: Discussionmentioning
confidence: 99%
“…Der bedeutsamste Risikofaktor für die Entstehung einer OA-Abhängigkeit ist eine frühere Suchterkrankung, bereits eine positive Familienanamnese erhöht die Wahrscheinlichkeit [60,62,65,84].…”
Section: Risikofaktorenunclassified